OBESITY AS A SPECIFIC OBSTACLE SUSTAINABLE SOCIAL AND ECONOMIC DEVELOPMENT - S. Kuzin; M. Karmanov (Вестник университета)
Аnnotation. At present, significant growth in the number of persons suffering from overweight is a serious problem for sustainable socio-economic development at the state, regional and municipal levels. In this regard great scientific and practical importance is the improvement of the methodology for applied studies of the extent and prevalence of obesity, as well as of losses caused by the deepening of such a negative process.